High frequency of colonization and absence of identifiable risk factors for methicillin-resistant Staphylococcus aureus (MRSA) in intensive care units in Brazil - Korn,Gustavo P. (2001)
Colonization of hospitalized patients with methicillin-resistant Staphylococcus aureus (MRSA) is of increasing concern. To evaluate this problem in Intensive Care Units (ICUs) in Brazil, we studied 100 patients admitted to two ICUs from April to June, 1997. Of the 100 patients, 70 were male, 53 were age 60 years or older, 55 were previously hospitalized, 78 were transferred to the ICU from other hospital units, 49 had received antibiotic therapy, and 66 had undergone recent surgery. Nasal and axillary swab cultures were obtained on admission and every 48 hours thereafter until discharge. MRSA were identified by plating any cultured S. aureus on Mueller-Hinton agar containing 6mug/ml of oxacillin. At the time of admission, 46 (46%) of the patients were colonized with MRSA. No associated risk factors for acquiring MRSA (age, previous hospitalization, prior surgery) could be identified. Of the 54 patients negative for MRSA on admission, 28 (52%) became colonized while in the ICU. Sixteen (22%) of the 74 colonized patients (colonized either on admission or during ICU stay) had associated respiratory or urinary tract infections due to MRSA, and 9 (56%) died. No correlation with special risk factors (invasive procedures, antibiotic use, age, chronic disease) was identified. MRSA occurred frequently, but there was minimal evidence of associated risk factors. Thus, control of MRSA cannot be accomplished by targeting special factors alone, but requires attention to preventing microbial spread in all areas. Of special concern is the high frequency of acquiring the organism in the ICU (52%). Education concerning the importance of hand washing, environmental surface cleaning, and barrier protection from infected patients is needed.